pySTARBURST99: The Next Generation of STARBURST99 - Calum Hawcroft; Claus Leitherer; Oskar Aranguré; John Chisholm; Sylvia Ekström; Sébastien Martinet; Lucimara P. Martins; Georges Meynet; Christophe Morisset; Andreas A. C. Sander; Aida Wofford (The Astrophysical Journal Supplement Series)
S tarburst 99 is a population synthesis code tailored to predict the integrated properties or observational characteristics of star-forming galaxies. Here, we present an update to S tarburst 99 where we port the code to Python and include new evolutionary tracks, both rotating and nonrotating, at a range of low-metallicity environments. We complement these tracks with a corresponding grid of new synthetic spectral energy distributions (SEDs). Additionally, we include both evolutionary and spectral models of stars up to 300–500 M _⊙ . Synthesis models made with the Python version of the code and new input stellar models are labeled pyS tarburst 99. We make new predictions for many properties, such as ionizing flux, SED, bolometric luminosity, wind power, hydrogen line equivalent widths (EWs), and the UV β -slope. These properties are all assessed over wider coverage in metallicity, mass, and resolution than in previous versions of S tarburst 99. A notable finding from these updates is an increase in H i ionizing flux of 0.3 dex in the first 2 Myr when increasing the upper mass limit from 120 to 300 M _⊙ . Changing metallicity has little impact on H i in the first 2 Myr (range of 0.015 dex from Z = 0.02 to 0.0), but lower metallicities have higher H i by 1 dex (compared to Z = 0.02–0.0004) at later times, with Z = 0.0 having even higher H i at later times. Rotating models have significantly higher H i than their equivalent nonrotating models at any time after 2 Myr. Similar trends are found for He i and He ii , bolometric luminosity and wind momentum, with more complex relations found for hydrogen line EWs and UV β -slopes.